JP4334894B2 - 固体電解質の製造方法 - Google Patents
固体電解質の製造方法 Download PDFInfo
- Publication number
- JP4334894B2 JP4334894B2 JP2003078066A JP2003078066A JP4334894B2 JP 4334894 B2 JP4334894 B2 JP 4334894B2 JP 2003078066 A JP2003078066 A JP 2003078066A JP 2003078066 A JP2003078066 A JP 2003078066A JP 4334894 B2 JP4334894 B2 JP 4334894B2
- Authority
- JP
- Japan
- Prior art keywords
- sintering
- solid electrolyte
- temperature
- mpa
- compression load
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Expired - Lifetime
Links
Images
Classifications
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
- C04B35/01—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics
- C04B35/48—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on zirconium or hafnium oxides, zirconates, zircon or hafnates
- C04B35/486—Fine ceramics
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
- C04B35/622—Forming processes; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
- C04B35/64—Burning or sintering processes
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
- C04B35/622—Forming processes; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
- C04B35/64—Burning or sintering processes
- C04B35/645—Pressure sintering
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M8/00—Fuel cells; Manufacture thereof
- H01M8/10—Fuel cells with solid electrolytes
- H01M8/12—Fuel cells with solid electrolytes operating at high temperature, e.g. with stabilised ZrO2 electrolyte
- H01M8/124—Fuel cells with solid electrolytes operating at high temperature, e.g. with stabilised ZrO2 electrolyte characterised by the process of manufacturing or by the material of the electrolyte
- H01M8/1246—Fuel cells with solid electrolytes operating at high temperature, e.g. with stabilised ZrO2 electrolyte characterised by the process of manufacturing or by the material of the electrolyte the electrolyte consisting of oxides
- H01M8/1253—Fuel cells with solid electrolytes operating at high temperature, e.g. with stabilised ZrO2 electrolyte characterised by the process of manufacturing or by the material of the electrolyte the electrolyte consisting of oxides the electrolyte containing zirconium oxide
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
- C04B2235/30—Constituents and secondary phases not being of a fibrous nature
- C04B2235/32—Metal oxides, mixed metal oxides, or oxide-forming salts thereof, e.g. carbonates, nitrates, (oxy)hydroxides, chlorides
- C04B2235/3224—Rare earth oxide or oxide forming salts thereof, e.g. scandium oxide
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
- C04B2235/30—Constituents and secondary phases not being of a fibrous nature
- C04B2235/44—Metal salt constituents or additives chosen for the nature of the anions, e.g. hydrides or acetylacetonate
- C04B2235/449—Organic acids, e.g. EDTA, citrate, acetate, oxalate
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/02—Composition of constituents of the starting material or of secondary phases of the final product
- C04B2235/50—Constituents or additives of the starting mixture chosen for their shape or used because of their shape or their physical appearance
- C04B2235/54—Particle size related information
- C04B2235/5418—Particle size related information expressed by the size of the particles or aggregates thereof
- C04B2235/5445—Particle size related information expressed by the size of the particles or aggregates thereof submicron sized, i.e. from 0,1 to 1 micron
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/656—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes characterised by specific heating conditions during heat treatment
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/656—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes characterised by specific heating conditions during heat treatment
- C04B2235/6562—Heating rate
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/656—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes characterised by specific heating conditions during heat treatment
- C04B2235/6567—Treatment time
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/658—Atmosphere during thermal treatment
- C04B2235/6581—Total pressure below 1 atmosphere, e.g. vacuum
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/66—Specific sintering techniques, e.g. centrifugal sintering
- C04B2235/661—Multi-step sintering
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/65—Aspects relating to heat treatments of ceramic bodies such as green ceramics or pre-sintered ceramics, e.g. burning, sintering or melting processes
- C04B2235/66—Specific sintering techniques, e.g. centrifugal sintering
- C04B2235/666—Applying a current during sintering, e.g. plasma sintering [SPS], electrical resistance heating or pulse electric current sintering [PECS]
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
- C04B2235/74—Physical characteristics
- C04B2235/76—Crystal structural characteristics, e.g. symmetry
- C04B2235/762—Cubic symmetry, e.g. beta-SiC
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
- C04B2235/74—Physical characteristics
- C04B2235/77—Density
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
- C04B2235/74—Physical characteristics
- C04B2235/78—Grain sizes and shapes, product microstructures, e.g. acicular grains, equiaxed grains, platelet-structures
- C04B2235/786—Micrometer sized grains, i.e. from 1 to 100 micron
-
- C—CHEMISTRY; METALLURGY
- C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
- C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
- C04B2235/00—Aspects relating to ceramic starting mixtures or sintered ceramic products
- C04B2235/70—Aspects relating to sintered or melt-casted ceramic products
- C04B2235/96—Properties of ceramic products, e.g. mechanical properties such as strength, toughness, wear resistance
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/30—Hydrogen technology
- Y02E60/50—Fuel cells
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02P—CLIMATE CHANGE MITIGATION TECHNOLOGIES IN THE PRODUCTION OR PROCESSING OF GOODS
- Y02P70/00—Climate change mitigation technologies in the production process for final industrial or consumer products
- Y02P70/50—Manufacturing or production processes characterised by the final manufactured product
Landscapes
- Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Manufacturing & Machinery (AREA)
- Ceramic Engineering (AREA)
- Materials Engineering (AREA)
- Structural Engineering (AREA)
- Organic Chemistry (AREA)
- Inorganic Chemistry (AREA)
- Life Sciences & Earth Sciences (AREA)
- Sustainable Development (AREA)
- Sustainable Energy (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Electrochemistry (AREA)
- General Chemical & Material Sciences (AREA)
- Composite Materials (AREA)
- Fuel Cell (AREA)
- Conductive Materials (AREA)
Description
【発明の属する技術分野】
本発明は、酸素センサや燃料電池に用いられるジルコニア質固体電解質に関する。
【0002】
【従来の技術】
固体電解質は、液漏れの心配がなく、伝導に寄与するイオンが特定のものであることから、電池、ガスセンサ等の各種素子の電子材料として極めて有効であり、最近研究開発が積極的に進められている。
【0003】
特に、セラミックス固体電解質燃料電池(SOFC)は進歩を続け、数KWのジルコニア質セラミックス燃料電池が数千時間の運転実績を積んでいる。SOFCは高温(>1000℃)で運転するために炭化水素系燃料を電池内で改質する事ができるため、高い燃焼効率(>60%)を得る事が可能である。
【0004】
一般に、SOFCの構成は固体電解質、アノード、カソードと中間層からなる。全ての構成材料は酸化還元雰囲気で安定であり適度なイオン導電性を有する必要がある。且つ構成材料の熱膨張係数が近く、アノードとカソードは多孔体でガスが透過できる事が必要である。また、電池材料の強度と靭性が高く安価である事が望ましく、さらには運転時の安定性の観点から、導電体の基本要件として同時に焼結された材料系が望ましい。
【0005】
現在、固体電解質に用いられる材料は安定化ZrO2が主流であり、安定化剤としては例えばCaO、MgOなどのアルカリ土類金属の酸化物、Sc2O3、Y2O3などの希土類酸化物等が用いられている。アルカリ土類金属のCaOをドープしたZrO2のイオン伝導特性値は800℃で0.01(S/cm)を示す。また、希土類酸化物、例えばY2O3、Yb2O3やGd2O3を単独でドープしたZrO2のイオン伝導度は、800℃で1×10-1〜1×10-2(S/cm)程度であるのに対し、650℃以下になると2×10-2(S/cm)以下に低下することが報告されている(例えば、非特許文献1参照。)。このような希土類酸化物を単独でドープすることによる安定化ジルコニアは1970年までにほとんど公知となっている。
【0006】
さらに、2種以上の希土類酸化物を添加した系として、3モルのY2O3−Yb2O3−La2O3から選ばれた2種の組み合わせや、3モルのGd2O3−Yb2O3が報告されている(例えば、特許文献1参照。)が、特性値は1000℃で0.005(S/cm)と高いものではない。
【0007】
最近、700℃以上で運転する燃料電池用の固体電解質としてスカンジウム酸化物で安定化したジルコニアが開示されている(例えば、特許文献2および3参照。)が、ジルコニア材料は600℃付近の温度で大幅に強度低下を起こすため、Al2O3などの元素を添加する手法の開発が主となっている。
【0008】
従来の固体電解質電池においては、単電池の出力が約1.1ボルトと限定されるため、高電力を得るには積層構造や並列構造をとることが必要である。しかし、このようなセラミックス電池は大型になり、セラミックス材料のシステム選択や大型電池の製造技術が非常に難しくなっている。そのため、このような大型セラミックス電池の燃焼器本体の容器などには、フェライト系ステンレスなど金属部品を有効に利用することが必要とされる。このような金属の有効利用のために、幅広い温度域において、特に低温(600〜800℃)においても活性で、かつ、イオン伝導率が高温(>1000℃)と同等である固体電解質材料が必要とされている。
【0009】
また、固体電解質は、温度約650℃付近で結晶が壊れやすいため、酸素センサに用いた場合は、上記温度域での粒界相の影響やエイジングの影響はそれほど重要ではないが、燃料電池に用いた場合には、酸化還元雰囲気下、高温における結晶相の安定化技術の確立や、高温での強度低下の防止が強く望まれている。これに関し、最近では結晶構造の安定化のためAl2O3を添加する方法が開示されている(例えば、特許文献4参照。)。
【0010】
一方、Sc2O3安定化ジルコニアにおいて、Sc2O3添加量が6〜9mol%であると立方晶と単斜晶が含まれた結晶相が観測されるが、そのイオン伝導度は希土類安定化ジルコニアと同レベルである。Sc2O3添加量が10mol%以上の場合には、700℃以上の温度では希土類安定化ジルコニアの値よりも数倍高い値となるが、500〜700℃以下では、相転移によりZr7Sc2O17で表される結晶相(本明細書中、「β相」とも称する。)が出現し、イオン伝導度は希土類安定化ジルコニアの値より2オーダー低下する。このような固体電解質を反応条件の変化する車載用燃料電池等に用いた場合には、低温域において使用ができなくなる、相転移に伴う膨張収縮によって破壊するなどの問題が生じる。
【0011】
したがって、Sc2O3安定化ジルコニアの低温域でのイオン伝導率の向上には、高温域の結晶相を安定化すること、すなわち、400〜900℃の間で相転移に伴う急激な伝導度変化を起こさないことが重要である。高温相を安定化させるためには結晶子径を小さく維持する方法が有力であり、そのために結晶子を小さく出来る製造方法、特に、結晶成長を起こさずに焼結できる手法の開発が強く望まれている。
【0012】
【特許文献1】
特開平06−116026号公報
【特許文献2】
特開平06−150943号公報
【特許文献3】
特開平10−097860号公報
【特許文献4】
特開平05−225820号公報
【非特許文献1】
H.Tannenberger et al., Proc.Int'l Etude Piles Combust,19-26(1965)
【0013】
【発明が解決しようとする課題】
本発明の目的は、上記従来の問題点を解決して、幅広い温度域、特に低温においてもイオン伝導度が高く、反応温度条件が変化しても相転移の発生が防止でき、結晶構造の安定性に優れる、酸素センサや燃料電池に使用可能な固体電解質を提供することにある。
【0014】
【課題を解決するための手段】
本発明は、組成成分が式:(1−x)ZrO2+xSc2O3(x=0.05〜0.15)で表される固体電解質の製造方法であって、焼結工程にスパークプラズマ法を用い、焼結過程における圧力を40MPa以下とし、かつ冷却過程における圧力を10〜15MPaとすることにより、結晶構造の安定性およびイオン伝導度、特に酸素イオン伝導度に優れる固体電解質が得られることを見出し、本発明を完成させるに至った。
【0015】
【発明の効果】
本発明による固体電解質材料の製造方法では、スパークプラズマ法の焼結工程における圧力を40MPa以下とすると同時に、冷却中には10〜15MPaの圧力に低減することによって、焼結後の粒子径が小さくクラックのない、イオン伝導性に優れた固体電解質を比較的簡便に得ることができる。
【0016】
また、本発明により得られる焼結体の結晶粒子は、平均粒子径が3μm以下であり、良好な焼結性を有すると共に導電特性にも優れた材料を提供できる。
【0017】
さらに、本発明によれば、特定の条件下でスパークプラズマ焼結を行うことにより、固体電解質材料を製造することができる。また、その焼結時間が大幅に短縮されたため、コストを大幅に低減することが可能になった。
【0018】
なお、本発明の製造方法により得られる固体電解質は、車載可能な固体電解質燃料電池の他にも、排出ガス中の酸素濃度検出センサの素材として利用することができる。
【0019】
【発明の実施の形態】
本発明の固体電解質の製造方法は、式:(1−x)ZrO2+xSc2O3(x=0.05〜0.15)で表される組成を有する固体電解質の製造方法である。ここで、Sc2O3のような希土類酸化物を添加した固溶体は「ホタル石」型構造をとるが、添加した元素の原子半径に依存した格子のひずみが生じ、添加元素ごとに異なる最適添加量が存在する。この最適添加量の範囲は狭く、添加元素の熱拡散により部分的に組成がずれた場合には特性が大きく変化するため、結晶構造を安定に維持し、イオン伝導性等の特性を低下させないことが必要である。
【0020】
この観点から、上記式において、xは0.05〜0.15である。xが0.05未満では単斜晶が増加するためイオン伝導度が低下する。一方、xが0.15超ではβ相が析出し高温域が安定化されないためである。
【0021】
本発明の固体電解質の製造方法は従来法と同じく、その製造工程は、焼結工程を有するものであれば特に限定されるものではないが、例えば具体的には、原料酸化物の混合工程、焼成合成工程、粉砕工程、焼結工程及び成形工程を経るものであってもよく、このうち特に焼結工程において、特定の条件下でスパークプラズマ法を用いることを特徴とする。
【0022】
スパークプラズマ焼結法を用いて低温で短時間に焼結させることにより、従来セラミックス製造に要していた時間を大幅に短縮させるとともに、生成する固体電解質の有するイオン伝導特性に優れる高性能な固体電解質を提供することができる。
【0023】
スパークプラズマ焼結法とは、原料粉末に圧縮負荷を加え、直流パルス電流を印加させて焼結する方法であり、放電焼結、通電焼結とも称される。より具体的には、例えば、原料粉末を圧縮して圧粉体とし、この圧粉体に負荷を加えながらON−OFFパルス状電流を通電するとともに、そのピーク電流およびパルス幅を調節して材料温度を制御しつつ圧縮焼結することができる。スパークプラズマ焼結機およびその作動原理等については、例えば、特許第3007929号(特開平10−251070号公報)を参照することができる。
【0024】
以下、本発明の固体電解質の製造方法を工程順に説明する。
【0025】
まず、Zr含有化合物粉末と、安定化剤としてのSc含有化合物粉末を、混合物中のScの割合が5〜15mol%となるように秤量して混合する。ここで秤量および混合の方法としては従来公知のものを用いることができる。また、この際に用いるZrおよびSc含有化合物の形態としては、特に制限されないが、クエン酸塩を用いることが好ましい。
【0026】
次いで、前記ZrおよびSc含有化合物を酸化してZrO2およびSc2O3を合成するために、前記混合物を大気中などの酸化雰囲気下で焼成する工程を含む。この際、焼成温度は900〜1000℃が好ましい。900℃未満では全てが分解せず、1000℃超では結晶子が過大となる。
【0027】
次いでこの焼成生成物を、溶媒中で粉砕してスラリーを得ることができる。ここで得られたスラリー中の粉砕混合物の平均粒子径は0.5μm以下であることが好ましい。0.5μm超では後の焼結工程が困難になるためである。用いる溶媒としてはエタノール、メタノールなどのアルコール、水等が挙げられる。粉砕条件は適宜決定することができるが、粉砕時間は24時間程度で十分である。また、粉砕に用いる装置としては、特に限定されないが、ボールミル、振動ミル等を用いることができる。
【0028】
上記で得られたスラリーを、ロータリーエバポレータ、噴霧乾燥器等を用いて乾燥することができる。
【0029】
次いで、上記で粉砕された微細粉末を、スパークプラズマ焼結法を用いて焼結させる。当該焼結時の圧縮負荷は40MPa以下が好ましく、20〜40MPaが特に好ましい。圧縮負荷を40MPa超にすると、焼結の緻密性は向上するものの焼結後の固体電解質内部にも微細なクラックが発生して、導電特性が発現しない可能性があるためである。また、焼結温度は1000〜1150℃が好ましく、1100℃が特に好ましい。1000℃未満では密度が低くなり、1150℃超では粒度が過大となる。さらに、焼結時間は60〜180分間が好ましく、30分間が特に好ましい。60分未満では密度が低くなり、180分超では粒度が過大となる。
【0030】
上記焼結過程においては、昇温速度を250℃/分以上にすることが好ましい。昇温速度を250℃/分未満で行うと、容器と反応して、焼結後に固体電解質中に不純物が混在してくる恐れがあるためである。
【0031】
また、その後の冷却過程においては、圧力を10〜15MPaに維持し、降温速度を200℃/分以下にすることが好ましい。圧力を上記の範囲に維持しながら行うことにより、固体電解質の破壊なしに焼結することができ、さらに、降温速度を200℃/分超にすると、焼結材料にクラックが発生して導電特性が発現しない可能性があるためである。
【0032】
さらに、本発明に係る固体電解質の製造方法においては、上記した焼結工程の後に、大気中で900〜1000℃、5〜15時間の熱処理を施してもよい。この処理により、より一層の良好な固体電解質を得ることができるためである。
【0033】
ここで、焼結後の結晶粒子の大きさは、その平均粒子径が好ましくは3μm未満である。この平均粒子径は、走査型電子顕微鏡(SEM)写真上において、任意の本数、例えば10本、の平行な直線が横切る粒子長の平均を画像装置を用いて求めたものである。平均粒子径を上記の範囲とすることで緻密で高強度な固体電解質を提供することができる。
【0034】
なお、焼結後において、焼結体を例えば円柱状等の成形体に加工し、密度を測定するとともに、X線回折法により成分を確認することができる。
【0035】
本発明において、得られる固体電解質の密度としては、真密度の95%以上が好ましい。これは酸素が透過することがないためである。
【0036】
また、本発明において、「立方晶率」とは、X線回折における、(220)面における代表ピーク強度(I)の比(I(立方晶:220)/{I(立方晶:220)+I(β相:220)})を百分率で表したものをいい、本発明においては、この立方晶率が90%以上であることが好ましい。これは、立方晶率が90%未満では電気伝導度が低いためである。
【0037】
本発明の方法により製造された固体電解質は、幅広い温度域において安定した結晶構造およびイオン伝導性を示すことから、部位により温度が異なる燃料電池に好適に用いることができる。また、温度変化の激しい自動車の排気管に取り付けられる酸素センサに用いた場合にも、安定した特性を示すことが期待できる。
【0038】
【実施例】
以下、本発明を実施例等によりさらに具体的に説明するが、本発明はこれらの実施例によって何ら限定されるものではない。
【0039】
実施例1
スカンジウム添加ジルコニア(セイミ化学製)を仮焼結することにより、一般式:(1−x)ZrO2+xSc2O3(x=0.06)で表される組成成分を有する固体電解質材料を得た。これを大気中1000℃で2時間焼成し、得られた焼成生成物をアルコール中でボールミルを用いて24時間程度の粉砕を行いスラリーを得、該スラリーをロータリーエバポレータを用いて乾燥した。次いで、その粉砕された微細粉末を、スパークプラズマ焼結法を用いて焼結させた。スパークプラズマ焼結時の条件は、真空下、圧縮負荷35MPa、1050℃で60分間であった。その焼結過程においては、昇温速度を300℃/分、圧縮負荷を35MPaに保持した。その後の冷却過程においては、圧縮負荷を10MPaに保持し、降温速度を150℃/分とした。
【0040】
さらに、上記した焼結工程の後、大気中で1000℃、10時間の熱処理を施した。
【0041】
なお、この焼結体の平均粒子径は、走査型電子顕微鏡(SEM)写真に撮り、平行な直線10本が横切る粒子長の平均を画像装置で求めた結果を採用した。また、500℃および700℃におけるイオン伝導度を測定した。
【0042】
次に、得られた焼結体を直径6mm、高さ8mmの円柱状物に加工し、その密度を測定するとともに、X線回折による成分測定を行った。
【0043】
その結果、密度は5.5×10-3kg/m3であった。また、合成度はX線回折の代表ピーク高さ(結晶比率100に対する)で判断し、100%合成されていた。
【0044】
上記の製造条件および得られた測定値を、表1に示す。
【0045】
実施例2〜4
実施例1におけるスパークプラズマ焼結を、表1に示す組成および焼結条件で行った以外は、実施例1と同様にしてそれぞれの焼結体を得た。得られた焼結体を実施例1と同様にして加工して測定し、得られた値をそれぞれ表1に示す。また、図1に、実施例4のX線回折による成分測定の結果のチャートを示す。
【0046】
比較例1および2
実施例1において粉砕された微細粉末を、大気中、1500℃で300分間焼結させて上記焼結体を得た。得られた焼結体を実施例1と同様にして加工して測定し、得られた値をそれぞれ表2に示す。また、図2に、比較例1のX線回折による成分測定の結果のチャートを示す。
【0047】
比較例3〜6
実施例1において、スパークプラズマ焼結工程の焼結時の圧縮負荷及び降温時の降温速度を、それぞれ表2に示す値にしたこと以外は、実施例1と同様にして焼結体を得た。また、実施例1と同様に加工して測定し、得られた値をそれぞれ表2に示す。また、図3に比較例3の、および図4に比較例6のX線回折による成分測定の結果のチャートを示す。
【0048】
なお、表1および2中の総合評価における○および×の判断基準は、イオン伝導度については、500℃で0.001(S/cm)以上、かつ700℃で0.02(S/cm)以上を○とした。また、立方晶率については90%以上を○とした。
【0049】
【表1】
【0050】
【表2】
【0051】
表1および2からわかる通り、本発明の製造方法によれば、平均粒子径が小さく、均一な結晶構造を有し、その結果イオン伝導度、特に酸素イオン伝導度に優れる固体電解質を得ることが可能である。
【図面の簡単な説明】
【図1】 実施例4のX線回折による成分測定の結果のチャートを示した図である。
【図2】 比較例1のX線回折による成分測定の結果のチャートを示した図である。
【図3】 比較例3のX線回折による成分測定の結果のチャートを示した図である。
【図4】 比較例6のX線回折による成分測定の結果のチャートを示した図である。
Claims (8)
- 組成成分が式:(1−x)ZrO2+xSc2O3(x=0.05〜0.15)で表される固体電解質の製造方法であって、焼結工程にスパークプラズマ法を用い、焼結過程における圧縮負荷が20〜40MPaであり、かつ焼結後冷却過程における圧縮負荷が10〜15MPaであることを特徴とする、固体電解質の製造方法。
- 前記焼結過程は、1000〜1150℃の温度で、30〜180分行われることを特徴とする、請求項1に記載の製造方法。
- 前記焼結過程において、昇温速度が250℃/分以上であることを特徴とする、請求項1または2に記載の製造方法。
- 前記焼結後冷却過程において、降温速度が200℃/分以下であることを特徴とする、請求項1〜3のいずれか1項に記載の製造方法。
- 金属元素およびアルカリ土類元素のクエン酸塩粉末の粉砕工程を含み、さらに焼結工程において同時に成形も行うことを特徴とする、請求項1〜4のいずれか1項に記載の製造方法。
- 前記焼結工程の終了後に、大気中において900〜1000℃の温度で5〜15時間の熱処理を行うことを特徴とする、請求項1〜5のいずれか1項に記載の製造方法。
- 前記固体電解質の、立方晶率([I(立方晶:220)/{I(立方晶:220)+I(β相:220)}]×100(%))が90%以上であることを特徴とする、請求項1〜6のいずれか1項に記載の製造方法。
- 組成成分が式:(1−x)ZrO2+xSc2O3(x=0.05〜0.15)で表される固体電解質の製造方法であって、焼結工程にスパークプラズマ法を用い、焼結過程における圧縮負荷が20〜40MPaであり、焼結温度が1000〜1150℃であり、焼結時間が30〜180分であり、昇温速度が250℃/分以上であり、かつ焼結後冷却過程における圧縮負荷が10〜15MPaであり、降温速度が200℃/分以下であることを特徴とする、固体電解質の製造方法。
Priority Applications (3)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2003078066A JP4334894B2 (ja) | 2003-03-20 | 2003-03-20 | 固体電解質の製造方法 |
| PCT/JP2004/003774 WO2004083147A1 (en) | 2003-03-20 | 2004-03-19 | Method of producing solid electrolyte and solid electrolyte |
| US10/549,290 US7438837B2 (en) | 2003-03-20 | 2004-03-19 | Method of producing solid electrolyte and solid electrolyte |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| JP2003078066A JP4334894B2 (ja) | 2003-03-20 | 2003-03-20 | 固体電解質の製造方法 |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| JP2004288445A JP2004288445A (ja) | 2004-10-14 |
| JP4334894B2 true JP4334894B2 (ja) | 2009-09-30 |
Family
ID=33027966
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| JP2003078066A Expired - Lifetime JP4334894B2 (ja) | 2003-03-20 | 2003-03-20 | 固体電解質の製造方法 |
Country Status (3)
| Country | Link |
|---|---|
| US (1) | US7438837B2 (ja) |
| JP (1) | JP4334894B2 (ja) |
| WO (1) | WO2004083147A1 (ja) |
Families Citing this family (12)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| US8617456B1 (en) | 2010-03-22 | 2013-12-31 | The United States Of America As Represented By The Secretary Of The Air Force | Bulk low-cost interface-defined laminated materials and their method of fabrication |
| US9120245B1 (en) | 2007-05-09 | 2015-09-01 | The United States Of America As Represented By The Secretary Of The Air Force | Methods for fabrication of parts from bulk low-cost interface-defined nanolaminated materials |
| US9162931B1 (en) * | 2007-05-09 | 2015-10-20 | The United States Of America As Represented By The Secretary Of The Air Force | Tailored interfaces between two dissimilar nano-materials and method of manufacture |
| JP2009085944A (ja) * | 2007-09-11 | 2009-04-23 | Yamaha Motor Co Ltd | ガスセンサ、空燃比制御装置および輸送機器 |
| KR101092754B1 (ko) | 2009-06-15 | 2011-12-09 | 한국생산기술연구원 | 고체산화물 연료전지의 연료극 및 그 제조방법 |
| FR2946979B1 (fr) * | 2009-06-19 | 2011-07-29 | Electricite De France | Fabrication de materiaux ceramiques autosupportes de faible epaisseur a base d'oxydes metalliques |
| ITVR20090153A1 (it) * | 2009-09-30 | 2011-04-01 | Eurocoating S P A | Procedimento per la realizzazione di materiale ceramico grezzo |
| US9601795B2 (en) * | 2009-10-23 | 2017-03-21 | Nippon Shokubai Co., Ltd. | Process for production of scandia-stabilized zirconia sheet, scandia-stabilized zirconia sheet obtained by the process, and scandia-stabilized zirconia sintered powder |
| FR2961350B1 (fr) * | 2010-06-11 | 2012-08-03 | Commissariat Energie Atomique | Procede de fabrication de cellules electrochimiques elementaires pour systemes electrochimiques producteurs d'energie ou d'hydrogene, notamment du type sofc et eht |
| FR2966455B1 (fr) | 2010-10-25 | 2013-05-17 | Commissariat Energie Atomique | Procede pour revetir une piece d'un revetement de protection contre l'oxydation |
| FR2983192B1 (fr) | 2011-11-25 | 2014-05-23 | Commissariat Energie Atomique | Procede pour revetir une piece d'un revetement de protection contre l'oxydation par une technique de depot chimique en phase vapeur, et revetement et piece |
| US12199326B2 (en) | 2019-05-10 | 2025-01-14 | The Regents Of The University Of California | Fabrication processes for metal-supported proton conducting solid oxide electrochemical devices |
Family Cites Families (12)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| JPS5833190B2 (ja) * | 1977-10-15 | 1983-07-18 | トヨタ自動車株式会社 | 酸素イオン導伝性固体電解質用安定化ジルコニア |
| JPS56109871A (en) * | 1980-01-29 | 1981-08-31 | Toyota Motor Co Ltd | Stabilized zirconia for oxygen ion conductive solid electrolyte |
| JPS56111455A (en) * | 1980-02-07 | 1981-09-03 | Nippon Denso Co Ltd | Solid electrolyte body for oxygen sensor |
| US4465778A (en) * | 1982-02-03 | 1984-08-14 | National Research Development Corporation | Sinterable fluorite oxide ceramics |
| US5591315A (en) * | 1987-03-13 | 1997-01-07 | The Standard Oil Company | Solid-component membranes electrochemical reactor components electrochemical reactors use of membranes reactor components and reactor for oxidation reactions |
| JPH05225820A (ja) | 1992-02-07 | 1993-09-03 | Nippon Telegr & Teleph Corp <Ntt> | イオン導伝体及び固体燃料電池 |
| JPH06150943A (ja) | 1992-11-05 | 1994-05-31 | Nippon Telegr & Teleph Corp <Ntt> | 酸素イオン導伝体及び固体燃料電池 |
| JP3411064B2 (ja) | 1993-06-17 | 2003-05-26 | 東邦瓦斯株式会社 | 固体電解質型燃料電池用固体電解質焼結体の製造方法 |
| JPH1097860A (ja) | 1996-09-20 | 1998-04-14 | Nippon Telegr & Teleph Corp <Ntt> | ゾルゲル法によるSc2O3、Al2O3添加ZrO2系固体電解質膜の作製法 |
| JP3007929B2 (ja) | 1997-01-08 | 2000-02-14 | 工業技術院長 | 酸化物微粒子の高密度焼結方法 |
| JP4771579B2 (ja) * | 2000-10-23 | 2011-09-14 | 東邦瓦斯株式会社 | 固体電解質型燃料電池 |
| JP4476689B2 (ja) * | 2004-05-11 | 2010-06-09 | 東邦瓦斯株式会社 | 低温作動型固体酸化物形燃料電池単セル |
-
2003
- 2003-03-20 JP JP2003078066A patent/JP4334894B2/ja not_active Expired - Lifetime
-
2004
- 2004-03-19 US US10/549,290 patent/US7438837B2/en not_active Expired - Fee Related
- 2004-03-19 WO PCT/JP2004/003774 patent/WO2004083147A1/en not_active Ceased
Also Published As
| Publication number | Publication date |
|---|---|
| JP2004288445A (ja) | 2004-10-14 |
| US7438837B2 (en) | 2008-10-21 |
| WO2004083147A1 (en) | 2004-09-30 |
| US20060172169A1 (en) | 2006-08-03 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| KR100226174B1 (ko) | 산소 이온 전도율이 높은 소결된 고체 전해질(Sintered solid electrolyte having a high oxygen-ion conductivity) | |
| KR101297067B1 (ko) | 고체 산화물 연료 전지 스택을 위한 코도핑된 ysz 전해질 | |
| Wang et al. | Two-step sintering of ultrafine-grained barium cerate proton conducting ceramics | |
| JPH05190180A (ja) | 固体電解質型燃料電池の空気電極体、その製造方法及び固体電解質型燃料電池の製造方法 | |
| JP5311913B2 (ja) | 高イオン導電性固体電解質材料の製造方法 | |
| JP2009091232A (ja) | 重合された無機−有機前駆物質溶液および焼結膜 | |
| JP2004288445A (ja) | 固体電解質の製造方法 | |
| JP3260988B2 (ja) | 固体電解質の製造方法 | |
| JP2004339035A (ja) | ランタンガレート系焼結体およびその製造方法、ならびにそれを用いた用途 | |
| JP3011387B2 (ja) | セラミックス及びそれを用いた円筒型固体電解質燃料電池並びに平板型固体電解質燃料電池 | |
| JP2011213588A (ja) | 高イオン伝導性固体電解質 | |
| JP5019323B2 (ja) | 希土類元素をドープしたセリア焼結体とその製造方法 | |
| JP5574881B2 (ja) | 固体酸化物型燃料電池用空気極材料粉末及びその製造方法 | |
| JP7055473B2 (ja) | 固体酸化物形セル用電極及びそれを用いた固体酸化物形セル | |
| JP2003123789A (ja) | 固体電解質材料、その製造方法およびそれを用いた固体電解質型燃料電池 | |
| JPH07126061A (ja) | マグネシア系焼結体及びその製造方法 | |
| JP2001072465A (ja) | 固体電解質、その製造方法、並びに該固体電解質を用いた燃料電池及び酸素センサー | |
| JP6562623B2 (ja) | 固体酸化物型燃料電池用混合空気極材料、及び、固体酸化物型燃料電池 | |
| JP3389407B2 (ja) | 導電性セラミックス及び燃料電池セル | |
| JP3598956B2 (ja) | ガレート複合酸化物固体電解質材料とその製造方法 | |
| JP4038628B2 (ja) | 酸化物イオン導電体およびその製造法並びに固体電解質型燃料電池 | |
| JP3193214B2 (ja) | 多孔質セラミック焼結体 | |
| JPH04170363A (ja) | 多結晶焼結体固体電解質 | |
| US8609565B1 (en) | Low-temperature protonic conduction for hydrogen-related energy applications employing nanostructured functional oxides | |
| JP2005259556A (ja) | 固体電解質及びその製造方法 |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| A621 | Written request for application examination |
Free format text: JAPANESE INTERMEDIATE CODE: A621 Effective date: 20050222 |
|
| A131 | Notification of reasons for refusal |
Free format text: JAPANESE INTERMEDIATE CODE: A131 Effective date: 20080205 |
|
| A521 | Request for written amendment filed |
Free format text: JAPANESE INTERMEDIATE CODE: A523 Effective date: 20080404 |
|
| TRDD | Decision of grant or rejection written | ||
| A01 | Written decision to grant a patent or to grant a registration (utility model) |
Free format text: JAPANESE INTERMEDIATE CODE: A01 Effective date: 20090609 |
|
| A01 | Written decision to grant a patent or to grant a registration (utility model) |
Free format text: JAPANESE INTERMEDIATE CODE: A01 |
|
| A61 | First payment of annual fees (during grant procedure) |
Free format text: JAPANESE INTERMEDIATE CODE: A61 Effective date: 20090624 |
|
| FPAY | Renewal fee payment (event date is renewal date of database) |
Free format text: PAYMENT UNTIL: 20120703 Year of fee payment: 3 |
|
| R150 | Certificate of patent or registration of utility model |
Ref document number: 4334894 Country of ref document: JP Free format text: JAPANESE INTERMEDIATE CODE: R150 Free format text: JAPANESE INTERMEDIATE CODE: R150 |
|
| FPAY | Renewal fee payment (event date is renewal date of database) |
Free format text: PAYMENT UNTIL: 20120703 Year of fee payment: 3 |
|
| FPAY | Renewal fee payment (event date is renewal date of database) |
Free format text: PAYMENT UNTIL: 20130703 Year of fee payment: 4 |
|
| R250 | Receipt of annual fees |
Free format text: JAPANESE INTERMEDIATE CODE: R250 |
|
| R250 | Receipt of annual fees |
Free format text: JAPANESE INTERMEDIATE CODE: R250 |
|
| R250 | Receipt of annual fees |
Free format text: JAPANESE INTERMEDIATE CODE: R250 |
|
| S533 | Written request for registration of change of name |
Free format text: JAPANESE INTERMEDIATE CODE: R313533 |
|
| R350 | Written notification of registration of transfer |
Free format text: JAPANESE INTERMEDIATE CODE: R350 |
|
| S111 | Request for change of ownership or part of ownership |
Free format text: JAPANESE INTERMEDIATE CODE: R313117 |
|
| R350 | Written notification of registration of transfer |
Free format text: JAPANESE INTERMEDIATE CODE: R350 |
|
| EXPY | Cancellation because of completion of term |
